Barriers and sources of information in prostate cancer screening at a South African hospital - Boitumelo M. Komane; Annah Mosalo (Journal of Public Health in Africa)
Background: Prostate cancer is a worldwide problem affecting men globally, particularly in low- and middle-income countries. However, research pertaining to barriers to screening uptake and sources of information regarding prostate cancer is limited in South Africa.